Bi‐allelic mutation in SEC16B alters collagen trafficking and increases ER stress - Ahmed El‐Gazzar; Barbara Voraberger; Frank Rauch; Mario Mairhofer; Katy Schmidt; Brecht Guillemyn; Goran Mitulović; Veronika Reiterer; Margot Haun; Michaela M Mayr; Johannes A Mayr; Susanne Kimeswenger; et al. (EMBO Molecular Medicine)
Abstract Osteogenesis imperfecta (OI) is a genetically and clinically heterogeneous disorder characterized by bone fragility and reduced bone mass generally caused by defects in type I collagen structure or defects in proteins interacting with collagen processing. We identified a homozygous missense mutation in SEC16B in a child with vertebral fractures, leg bowing, short stature, muscular hypotonia, and bone densitometric and histomorphometric features in keeping with OI with distinct ultrastructural features. In line with the putative function of SEC16B as a regulator of trafficking between the ER and the Golgi complex, we showed that patient fibroblasts accumulated type I procollagen in the ER and exhibited a general trafficking defect at the level of the ER. Consequently, patient fibroblasts exhibited ER stress, enhanced autophagosome formation, and higher levels of apoptosis. Transfection of wild‐type SEC16B into patient cells rescued the collagen trafficking. Mechanistically, we show that the defect is a consequence of reduced SEC16B expression, rather than due to alterations in protein function. These data suggest SEC16B as a recessive candidate gene for OI.